O Tracoma no Município de Botucatu - Estado de São Paulo: medidas de Detecção, Educação em Saúde, Prevenção e Tratamento - Meneghim, Roberta Lilian Fernandes de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Trachoma still ranks among the major causes of blindness in the world, being the leading cause of preventable blindness and the leading cause of corneal blindness. In Brazil, for several years, it was believed that the disease had been eradicated, which prevented the searching and the teaching of the disease in medical schools and decreased the active search, increasing the number of untreated people and affected by the disease. Furthermore, the maintenance factors of the disease in the environment must be detected for its better control. Based on these facts, this study was developed with the objectives of promoting health education; prevent blindness from trachoma detecting and treating cases of the disease; describe the socioeconomic profile of disease carriers in Botucatu; search for the presence of vectors of the disease and for the bacterium which causes trachoma in these vectors. Methods: A cross-sectional study was conducted in the city of Botucatu, state of São Paulo - Brazil in 2010. A group of eight students from the graduation course in Medicine or in Nursing and two health workers was trained by two ophthalmologists to detect and how to treat trachoma in the population, according to the recommendations of the World Health Organization (WHO). After training, a fieldwork was conducted by the exam of a random sample of 3568 children, calculated based on historical data of the prevalence of trachoma in Botucatu and on the number of children enrolled in primary education in municipal schools. The primary unit of the sample was the class, and all children from the selected class were examined. The diagnosis was clinical, with eyelid eversion looking for follicles on the superior tarsal conjunctiva by using a 2.5-fold increase binocular magnifier lenses and artificial light (flashlight). Children with inflammatory trachoma were treated with Azithromycin, 20 mg/kg of weight and visited at home for a socioeconomic questionnaire ...

O tracoma ainda figura entre as grandes causas de cegueira do mundo, sendo a principal causa de cegueira evitável e a principal causa de cegueira corneana. No Brasil, por vários anos, acreditou-se que a doença havia sido erradicada, o que impediu seu ensino nas escolas médicas e diminuiu a busca ativa, aumentando o número de pessoas não tratadas e portadoras da doença. Além disso, os fatores que mantém a doença no meio ambiente precisam ser detectados para melhor controle da mesma. Diante destes fatos, desenvolveu-se este estudo com os objetivos de promover educação em saúde; prevenir a cegueira por tracoma detectando e tratando os casos da doença; descrever o perfil socioeconômico dos portadores da doença no município de Botucatu; pesquisar a presença de vetores da doença e da bactéria causadora de tracoma nesses vetores. Material e Métodos: Estudo transversal conduzido na cidade de Botucatu, estado de São Paulo - Brasil no ano de 2010. Um grupo composto por oito estudantes do curso de graduação em Medicina ou Enfermagem e duas agentes de saúde foi treinado por dois oftalmologistas para detectar e tratar o tracoma na população, segundo as recomendações da Organização Mundial de Saúde (OMS). Após treinamento, foi realizado trabalho de campo, com exame de uma amostra aleatorizada de 3568 crianças, calculada baseando-se nos dados históricos da prevalência de tracoma em Botucatu e no número de crianças matriculadas no ensino fundamental das escolas municipais. A unidade primária de amostra foi a classe, examinado-se todas as crianças da classe sorteada. O diagnóstico foi clínico, com eversão palpebral à procura de folículos em conjuntivas tarsais superiores usando-se lupa binocular de 2,5 vezes de aumento e iluminação artificial (lanterna). As crianças com tracoma inflamatório foram tratadas com Azitromicina, 20 mg/kg de peso e visitadas em suas casas para aplicação de um questionário...
Keywords: Conjuntivite granulosa; Conjuntiva - Doenças; Estudos transversais; Trachoma